RESPONSE GROWTH AND YIELD OF PEANUTS CROP TO VARIOUS DOSES OF BIOCHAR CORNCOBS OF MAIZE ON ULTISOL SOIL - SUHARTARTO, AGUNG (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aimed to obtain the best dose of corncob biochar on the growth and yield of peanut crop on ultisol soil. This study began from 31 May to September 22, 2018. Research was carried out in the Jl.Purnama Agung VII, Komplek Pondok Agung Permata, Kelurahan Parit tokaya, Pontianak Selatan. The methodology that was in study used Completely Randomized Design consisted of 5 treatments, 5 replications and each replication there were 4 plant samples. The Treatment is as follows: (b1) 400 g/polybag, (b2) 800 g/polybag, (b3) 1200 g/polybag, (b4) 1600 g/polybag and (b5) 2000 g/polybag. The variables observed in this study were the volume of the root (cm3), the amount of chlorophyll the leaves (spad unit), the width of the leaves (cm2), dry weight of plants (g), number of pods per plant (pods), weight of seed dry per plant (g), and weigh as 100 the seeds of dry (g). The research results show that growth and result of peanut the best shown by the provision of corncobs biochar with doses 800 g/ polybag.Keywords: biochar corncobs, peanuts, soil of pmk